A Rare Pulmonary Infection Case: Pulmonary Actinomycosis - Muhammet GÜLHAN (Flora Infeksiyon Hastalıkları ve Klinik Mikrobiyoloji Dergisi, 2016)
Actinomycosis is a slowly progressive disease which is caused by gram-positive anaerobic bacteria of the family Actinomyceataceae. Actinomycesisraelii is the most common agent of actinomycosis. Pulmonary actinomycosis clinically or radiologically imitates tuberculosis, pulmonary abscess or lung cancer. These similarities principally lead to misdiagnosis or delayed diagnosis. Predisposing factors which emanate the illness include alcoholism, bad-oral hygiene, gingiva diseases, face traumata, diabetes mellitus, emphysema, chronic bronchitis, and bronchiectasis. A 57-year-old male patient presented with ongoing sputum and dyspnea. The non-smoker patient’s physical examination indicated that right central and sub-regional lung had rales. Whole blood values and pulmonary function test were normal. On chest X-Ray, there was a nonhomogeneous density beat on the right lower zone. The patient who did not respond to non-specific antibiotic treatment given in two weeks and tuberculosis and lung cancer was evaluated with bronchoscopy. Pathological examination showed actinomyces colonies, squamous cells, lymphocytes, macrophages, and neutrophils. Oral amoxicillin was started after IV ampicillin/sulbactam treatment . In the 6th month of treatment, the symptoms of the patient and radiologic findings receded. Patients with infiltrations on chest radiography and with no response to antibiotic treatment should not be forgotten to be examined for tuberculosis, lung cancer and rarely seen Actinomycosis infection for distinctive diagnosis.